Limited Training Through E-Training To Improve Competency of the Head of School at the Head's Working Meeting Schools for SMP and MTs in Bengkulu City - Connie Connie; Eko Risdianto (Asosiasi Profesi Multimedia Indonesia, 2022)
Limited training through e-education aims to improve the competence of school principals in the work consultations for principals of SMP and Mts Bengkulu City. The target audience for this service is the Principals of the Bengkulu City Middle School and MTs who are members of the School Principal Working Consultation as many as 18 people. The implementation method is carried out by three methods namely training, orientation, and practice. This Principal Strengthening Training uses the MOOCs-based E-Training system. The training referred to here consists of activities providing orientation on what teachers need in order to improve the competence of school principals in accordance with the Regulation of the Minister of National Education. Limited Training Through E-Training to improve the competence of school principals at the Bengkulu City Junior High School Headmaster's Working Meeting is the right activity and is very in line with current learning needs. This training has been well implemented and received a positive response from the trainees.